2012
DOI: 10.1111/j.1741-3729.2012.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Do You See What I See? Parent and Child Reports of Parental Monitoring of Media

Abstract: Research on parental monitoring of children's media use suggests parents can reduce the negative effects of media exposure on children, although this research is rarely conducted with elementary school children and leaves open questions about whether parents or children are better reporters. Participants were 1,323 children, their parents, and teachers. Parents and children reported on four aspects of monitoring for TV and video games: co‐using, limit setting on amount, limit setting on content, and active med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
2
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 91 publications
(258 reference statements)
10
138
2
14
Order By: Relevance
“…With regard to the marital household status, also no differences appeared between the four types of media users, i.e., single parents and married parents were evenly distributed among lower and higher use families. Former studies had indicated that single parents are less restrictive on their children's media use (Gentile et al, 2012) and probably therefore have children who are higher users of media as compared to children in intact families (Cingel & Krcmar, 2013;Vandewater et al, 2007). Maybe, marital status and number of siblings are not strongly related to the parent's own media consumption when children are still rather young, as compared to when children get older and more demanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the marital household status, also no differences appeared between the four types of media users, i.e., single parents and married parents were evenly distributed among lower and higher use families. Former studies had indicated that single parents are less restrictive on their children's media use (Gentile et al, 2012) and probably therefore have children who are higher users of media as compared to children in intact families (Cingel & Krcmar, 2013;Vandewater et al, 2007). Maybe, marital status and number of siblings are not strongly related to the parent's own media consumption when children are still rather young, as compared to when children get older and more demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Next, in single parent families young children make more use of media, both educational and non-educational (Cingel & Krcmar, 2013;Vandewater et al, 2007), but this could also be related to the parent's media use. Single parents experience more stress in parenting (McLoyd, 1998), are usually less involved in their children's media use (Warren, 2005) and are less restrictive on their children's media time and content choices (Gentile, Nathanson, Rasmussen, Reimer, & Walsh, 2012). Thus, single parents may not only more often allow their children to own and use media devices, but to use media more often to entertain themselves, therefore comprising higher use families (H 2c ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While restrictive mediation, active mediation, and co-use strategies originate from previous studies (Gentile et al, 2012;Nikken & Jansz, 2006;Warren, 2001), participatory learning and distant mediation are combinations of previously separate strategies. The first one combines both active mediation and co-use, and implies that parents invest in digital knowledge and skills.…”
Section: Parental Mediationmentioning
confidence: 99%
“…parents having instructive or evaluative conversations with their children in order to explain or discuss children's use of digital media), and (3) co-use (i.e. parents sharing media activities with their children, driven by a common interest) (Gentile, Nathanson, Rasmussen, Reimer, & Walsh, 2012;Nikken & Jansz, 2006;Warren, 2001). …”
Section: Parental Mediationmentioning
confidence: 99%
“…Halpenny et al (2010) describe two types of parenting: (1) Authoritative parenting which is characterised by warmth and reasoning, exercised with younger children (2) Authoritarian parenting is characterised by high levels of control, exercised with adolescents. In terms of parenting and mediation of media/technology use, a variety of academic projects (Gentile et al, 2012;Kundanis, 2003) report three different media mediation styles: (1) Active: talking to the child about the media/technologies and explaining its mechanics to them (2) Restrictive: Setting strict rules of what can be accessed and in what amounts by the child (3) Coviewing: Only participating in the child's media use. As Kundanis (2003) and Gentile et al(2012) outline, active mediation is usually seen as optimal due to its beneficial effects on children's understanding of the media and technologies.…”
Section: Sociology Of Family/ Family Studiesmentioning
confidence: 99%